Using the Flexor Reflex in a Chronic Stroke Patient for Gait Improvement: A Case Report - Salzmann, Christian; Sehle, Aida; Liepert, Joachim (Frontiers in Neurology, 2021)
The flexor reflex or withdrawal reflex can be elicited by electrical stimulation of the sole of the foot, which serves as a reflex to protect the stimulated limb against tissue damage and consists of flexion movements in the hip, knee, and ankle joint. Triggering this reflex might improve walking abilities in hemiparetic patients. We report the first case of a chronic stroke patient with the most severe impairment of walking. She was examined with and without flexor reflex activation by the Incedo® system. Tests included a 10-m walk and a 2-min walk at baseline, after 3 weeks of training with the Incedo® system and after a follow-up 3 weeks later. Moreover, a kinematic gait analysis was done before and after the training period. At baseline, activation of the flexor reflex induced an improved gait velocity. After the training period, the patient walked twice as fast compared with baseline. Her gait velocity without Incedo® was faster than the gait velocity with Incedo® at baseline. Examination at follow-up indicated that the improvements remained almost unchanged. The kinematic analysis showed an improved stride length and gait velocity during flexor reflex activation. Initially, the foot was elevated higher above the ground during flexor reflex activation. In conclusion, this first case report of a chronic stroke patient demonstrates that flexor reflex activation is feasible and improves gait parameters despite severe impairment of walking abilities.